Modelling of acetaldehyde and acetic acid combustion - Wako, Fekadu Mosisa; Pio, Gianmaria; Salzano, Ernesto (Combustion theory and modelling, 2023)
Despite the beneficial impact of biofuels on most regulated pollutants and carbon dioxide emissions, their combustion results in the generation of undesired pollutants, such as acetaldehyde and acetic acid. To better understand the chemistry of these species, detailed chemical kinetic models deriving from two alternative strategies for mechanism generation were developed and validated against available data. The first model represents a semi-lumped mechanism comprising 89 species and 366 reactions, whereas the latter is automatically generated to aggregate elemental steps based on a rate-based algorithm, and it contains 541 species and 27,334 reactions. Under the studied conditions, the two kinetic models fairly predicted ignition delay times and laminar burning velocity data of acetic acid and acetaldehyde. Few discrepancies were observed for ignition delay time at temperatures lower than 1300 K. However, the overall agreement between experimental measurements and numerical estimations allowed for the use of the two kinetic models to unravel the chemistry of the investigated species. Highlights Identification of key primary reactions for acetic acid and acetaldehyde Integration of an existing kinetic mechanism with selected reactions Development of a detailed kinetic mechanism through an automated algorithm Comparison of experimental and numerical data for overall reactivity Analysis of the chemistry of acetic acid and acetaldehyde